The Perception of Disability Among Mothers Living With a Child With Cerebral Palsy in Saudi Arabia. (April 2019) - Mohamed Madi, Sanaa; Mandy, Anne; Aranda, Kay
The purpose of this study was to explore the perceptions of disability among Saudi mothers and to understand the implication of the meaning for the mothers of children with disability. A critical ethnographic approach was employed using focus groups and follow-up interviews with the mothers. Three primary themes were identified that specifically influenced and affected the mothers' experiences: (a) culture and religion, (b) motherhood and disability, and (c) community stigma and discrimination. The study reveals much-needed knowledge and sheds light on a topic, the details of which are rarely available in research literature from the Middle East. The findings further endorse the need for clinicians to listen to the mothers to consider their beliefs and the impact of these beliefs on their experiences. This, in turn, may provide a valuable conceptual lens for health care practitioners to use the family-centered model when working with cerebral palsy children.